Investigating the effect of the CPOT-based pain management program on the pain intensity and dose adjustment of analgesics in mechanically ventilated patients: A randomized clinical trial - Fatemeh Kouhi; Razieh Froutan; Ahmad Bagheri Moghaddam (Tehran University of Medical Sciences, 2023)
Background & Aim: This research was conducted to determine the effect of a pain management program based on the Critical Care Pain Observation Tool (CPOT) on the pain intensity and adjusting the dosage of analgesics in mechanically ventilated patients hospitalized in intensive care units. Methods & Materials: This randomized controlled clinical trial was conducted during 2019-2022 on 70 mechanically ventilated patients admitted to ICUs of the Imam Reza Hospital, Mashhad, Iran. In the intervention group, patients' pain intensity was measured during endotracheal suctioning using CPOT. Then the dosage of analgesics was adjusted based on the assessed pain level. The pain level was evaluated in the control group according to the department's routine. Data were analyzed using two-way repeated measures analysis of variance (RMANOVA). Results: CPOT and BPS showed a strong correlation (r>0.9, Pvalue<0.001) between the two pain intensity instruments. Based on the results of RMANOVA, a significant trend of pain intensity measures was observed during all three suctions (measurement effect P<0.05), which was different between the two groups (interaction effect P<0.05). The Sidak post hoc test results showed a significant difference in pain intensity measures between the intervention and control groups during all three suctions and 5 and 15 minutes after suctions (all P-values<0.05). Also, significant intervention effects were observed regarding the amount of analgesics prescribed in terms of total fentanyl blouse, total infused Fentanyl, and total Fentanyl (all P-values<0.05). Conclusion: Using CPOT is a positive step in the evaluation and control of dosage adjustment of analgesic medications for patients with mechanical ventilation.